FOLKLORE ART, AS AN IMPORTANT FACTOR IN THE STUDY OF NATIONAL VALUES - R. N. Rakhimov (Western European Studies, 2025)
this article examines folk art in the education of young people, the role of folk songs, human qualities, spiritual worldview, deep philosophical and social thinking, as well as decisions aimed at the development of folk art in our country and valuable ideas about the interaction of mudhas with moral education, spiritual maturity of the individual
Keywords: music; elegance; morality; song